The role of the citizen and participatory data in information model-based planning in Finland - Nummi, Pilvi; Harsia-Mikkola, Eveliina; Mattila, Hanna (Informa UK Limited, 2026)
Applying a socio-technical systems approach, this article examines how transitioning to a nationally interoperable land-use planning system affects participatory planning in Finland. We conducted a constructive study, gathering insights from experts in participatory planning, digitalisation specialists, and government representatives through surveys and interviews. Our findings demonstrate that the transformation influences participatory planning. Participatory information is considered an essential component of planning data, highlighting the need for its comprehensive and multidimensional definition and description within the national plan information model. We propose a conceptual model for participatory data and recommendations on how it should be represented in the plan information model.